2023
DOI: 10.1038/s41467-023-36503-2
|View full text |Cite|
|
Sign up to set email alerts
|

Genomics and biochemical analyses reveal a metabolon key to β-L-ODAP biosynthesis in Lathyrus sativus

Abstract: Grass pea (Lathyrus sativus L.) is a rich source of protein cultivated as an insurance crop in Ethiopia, Eritrea, India, Bangladesh, and Nepal. Its resilience to both drought and flooding makes it a promising crop for ensuring food security in a changing climate. The lack of genetic resources and the crop’s association with the disease neurolathyrism have limited the cultivation of grass pea. Here, we present an annotated, long read-based assembly of the 6.5 Gbp L. sativus genome. Using this genome sequence, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 79 publications
0
17
0
Order By: Relevance
“…However, overexpression of the pointmutated LsSAT2 in L. sativus or achievement of single base transition/transversion at target sites via plant base editing or prime editing is still expectant to facilitate the genetic site validation of LsSAT2 activity and further crop improvement. Very recently, studies verifying the links of an oxalyl-CoA synthetase (acyl-activating enzyme 3, AAE3) 41 and β-ODAP synthase (BOS) 42 to β-ODAP biosynthesis in L. sativus and the presence of β-ODAP in Pisum sativum L. 43 provide an interesting clue to reveal insights into β-ODAP biosynthesis in these two sister species via comparative genomics. 41,44−46 ■ ASSOCIATED CONTENT * sı Supporting Information…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, overexpression of the pointmutated LsSAT2 in L. sativus or achievement of single base transition/transversion at target sites via plant base editing or prime editing is still expectant to facilitate the genetic site validation of LsSAT2 activity and further crop improvement. Very recently, studies verifying the links of an oxalyl-CoA synthetase (acyl-activating enzyme 3, AAE3) 41 and β-ODAP synthase (BOS) 42 to β-ODAP biosynthesis in L. sativus and the presence of β-ODAP in Pisum sativum L. 43 provide an interesting clue to reveal insights into β-ODAP biosynthesis in these two sister species via comparative genomics. 41,44−46 ■ ASSOCIATED CONTENT * sı Supporting Information…”
Section: ■ Discussionmentioning
confidence: 99%
“…sativus or achievement of single base transition/transversion at target sites via plant base editing or prime editing is still expectant to facilitate the genetic site validation of LsSAT2 activity and further crop improvement. Very recently, studies verifying the links of an oxalyl-CoA synthetase (acyl-activating enzyme 3, AAE3) and β-ODAP synthase (BOS) to β-ODAP biosynthesis in L. sativus and the presence of β-ODAP in Pisum sativum L .…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis of these BAHD-AT genes revealed that a particular clade has expanded in the legumes significantly. This clade encompasses nine members displaying different tissue-specific expression in grass peas (Edwards et al, 2023). Among them, BAHD-AT3 displays higher expression over the other isoforms of the clade, with its highest abundance in the late pods (Edwards et al, 2023).…”
Section: Figurementioning
confidence: 99%
“…This clade encompasses nine members displaying different tissue-specific expression in grass peas (Edwards et al, 2023). Among them, BAHD-AT3 displays higher expression over the other isoforms of the clade, with its highest abundance in the late pods (Edwards et al, 2023). Therefore, we hypothesized that loss-of-function mutation of this gene might significantly reduce the β-ODAP content in grass pea seeds.…”
Section: Figurementioning
confidence: 99%
“…The genome of Lathyrus sativus has largely been unexplored as the genome sequences were not available until recently (Edwards et al,2023;Rajarammohan et al, 2023). Only few -omics studies have been carried out to understand the underlying mechanisms of ODAP synthesis (Almeida et al, 2014(Almeida et al, , 2015Hao et al, 2017;Verma et al, 2022;Xu et al, 2018;Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%